FACTORS AFFECTING JOB MOTIVATION AMONG NURSES OF A TERTIARY CARE HOSPITAL OF LAHORE - WARIS , S; BASHIR , M; IMTIAZ , M; TASNEEM , SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Job motivation is critical for ensuring quality patient care and retaining skilled nursing staff, particularly in resource-constrained settings like Pakistan. Understanding factors influencing motivation is essential for developing effective strategies to enhance nurse performance and satisfaction. Objective: To evaluate factors affecting job motivation among nurses at a tertiary care hospital in Lahore, focusing on intrinsic and extrinsic motivators. Methods: A descriptive cross-sectional study was conducted among 222 nurses using a structured questionnaire. Data were analyzed using SPSS version 26, with descriptive statistics summarizing the findings. Results: The majority of nurses (68.9%) felt recognized for their hard work, and 72.5% acknowledged career advancement opportunities. High satisfaction was reported with work hours (93.3%) and workplace safety (81.9%). Performance appraisal systems were rated positively, with 69.3% indicating that results were used for promotions. However, 21.7% were dissatisfied with remuneration, and only 32% reported access to continuing education opportunities. Conclusion: Recognition, career advancement, and a positive work environment significantly influence job motivation among nurses. Addressing challenges related to remuneration and staff development opportunities is essential for fostering a motivated and satisfied nursing workforce in Pakistan.